Sex differences in management and outcomes in pheochromocytomas and paragangliomas - Dahl, Måns A. J.; Calissendorff, Jan; Falhammar, Henrik (Frontiers in Endocrinology, 2025)
PurposeThe aim of this study was to investigate sex differences in the management and outcomes of patients with pheochromocytomas and paragangliomas (PPGLs).MethodsThis is a retrospective cohort study including all patients diagnosed with PPGLs attending the Department of Endocrinology at Karolinska University Hospital between June 2005 and August 2024. The collected data included patient characteristics, biochemical, genetical, pharmacological and vital parameters noted during initial PPGL presentation and during follow-up, including survival.ResultsIn total, 196 patients diagnosed with PPGLs (108 females and 88 males) were included. Paragangliomas were more prevalent in females than in males (23.1% vs 11.4%, P=0.04). Females required a lower final dose of preoperative phenoxybenzamine (50.8 ± 19.8 vs 87.5 ± 75.7 mg, P=0.04), while the final dose of preoperative doxazosin was non-significant lower (22.3 ± 13.6 vs 26.0 ± 13.9 mg, P=0.07). Moreover, females were less likely having laparoscopic surgery than males (55.2% vs 71.1%, P=0.03). After surgery, more females achieved remission from their type 2 diabetes compared to males (23.4% vs 11.8%, P=0.04). Despite similar age at diagnosis and similar follow-up time, no sex differences were identified in metastasis risk, blood pressure outcomes after surgery, or survival.ConclusionFemales presented more often with paragangliomas which may explain why they were less likely to have laparoscopic surgery. Remission of type 2 diabetes occurred more commonly in females after surgery. Most other outcomes were similar between sexes. More research is needed to explore differences in outcomes between sexes in PPGLs.